Respuesta :

Step-by-step explanation:

5x-4=-3-x

5x+x=4+(-3)

6x=1

x=1/6

Answer:

[tex] \boxed{ \huge{ \bold{ \sf{x = 0.16}}}}[/tex]

Step-by-step explanation:

[tex] \sf{5x - 4 = - 3 - x}[/tex]

Move constant to R.H.S and change it's sign

Similarly, Move variable to L.H.S and change it's sign

⇒[tex] \sf{5x + x = - 3 + 4}[/tex]

Collect like terms

⇒[tex] \sf{6x = - 3 + 4}[/tex]

Calculate

⇒[tex] \sf{6x = 1}[/tex]

Divide both sides of the equation by 6

⇒[tex] \sf{ \frac{6x}{6} = \frac{1}{6} }[/tex]

Calculate

⇒[tex] \sf{x = 0.16}[/tex]

Hope I helped!

Best regards!!

ACCESS MORE